2020
DOI: 10.21203/rs.3.rs-36991/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exogenous Polyunsaturated Fatty Acids (PUFAs) Promote Changes in Growth, Phospholipid Composition, Membrane Permeability and Virulence Phenotypes in Escherichia Coli

Abstract: Background: The utilization of exogenous fatty acids by Gram-negative bacteria has been linked to many cellular processes, including fatty acid oxidation for metabolic gain, assimilation into membrane phospholipids, and control of phenotypes associated with virulence. The expanded fatty acid handling capabilities have been demonstrated in several bacteria of medical importance; however, a survey of the polyunsaturated fatty acid responses in the model organism Escherichia coli has not been performed. The curre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The results of permeability testing using CV and EtBr showed significant ( p < .001) differences depending on fatty acid; however, there were several differences between hydrophobic compounds. The prevailing theme is that, regardless of A‐layer, several PUFAs caused elevated permeability, as has been observed with equivalent methodology in other Gram‐negative bacteria such as E. coli and Klebsiella pneumoniae (Herndon et al, 2020; Hobby et al, 2019). However, other Gram‐negative bacteria, such as Acinetobacter baumannii , Pseudomonas aeruginosa and several Vibrio spp ., display the opposite trend (Baker et al, 2018; Eder et al, 2017; Moravec et al, 2017; Smith et al, 2021), suggesting different coping mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…The results of permeability testing using CV and EtBr showed significant ( p < .001) differences depending on fatty acid; however, there were several differences between hydrophobic compounds. The prevailing theme is that, regardless of A‐layer, several PUFAs caused elevated permeability, as has been observed with equivalent methodology in other Gram‐negative bacteria such as E. coli and Klebsiella pneumoniae (Herndon et al, 2020; Hobby et al, 2019). However, other Gram‐negative bacteria, such as Acinetobacter baumannii , Pseudomonas aeruginosa and several Vibrio spp ., display the opposite trend (Baker et al, 2018; Eder et al, 2017; Moravec et al, 2017; Smith et al, 2021), suggesting different coping mechanisms (e.g.…”
Section: Discussionmentioning
confidence: 82%
“…Analysis of the changes in membrane fatty acid content after exogenous fatty acid addition indicated that exogenous fatty acids can help cells’ de novo biosynthesis of membrane fatty acids. The reason for the further increase in unsaturated fatty acids contents may be the strengthened synthesis of fatty acids from saturated to unsaturated to improve salt tolerance 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…The reason for the further increase in unsaturated fatty acids contents may be the strengthened synthesis of fatty acids from saturated to unsaturated to improve salt tolerance. 35,36 Membrane fluidity is an important metric of membrane health, and it can be changed by growth condition changes. 37 As shown in Fig.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%